Marcus Valerius Maximianus: the Hero of the Marcomannic Wars - Olędzki, Marek (International Studies. Interdisciplinary Political and Cultural Journal, 2022)
The article provides a reconstructed biography of an outstanding Roman, M. V. Maximianus who became famous for his many heroic deeds in the period of the so-called Marcomannic wars. The reconstruction is undertaken on the basis of two sources of major importance, both of them inscriptions. The first of them was discovered in today’s Slovak town of Trenčin, the other in Zana in Algieria. Significantly, their content is mutually enriching and complementary. A pretext for the discussion was the conversation with the Jubilarian on the authenticity of the character of Maximus created by Russel Crowe in the film “Gladiator”, contrasted in the article with the historical figure of Maximianus.